Value of Oral Proton Pump Inhibitors in Acute, Nonvariceal Upper Gastrointestinal Bleeding: A Network Meta-Analysis. Issue 8 (September 2017) - Rodriguez, Eduardo A.; Donath, Elie; Waljee, Akbar K.; Sussman, Daniel A.
Abstract : Background: Intravenous (IV) proton pump inhibitors (PPI) are the standard medical treatment in acute nonvariceal upper gastrointestinal bleeding (ANVGIB). Optimal route of PPI delivery has been questioned. Aim: The aim was to perform a systematic review and network meta-analysis for the endpoints of risk of rebleeding, length of stay (LOS), surgery (ROS), mortality, and total units of blood transfused (UBT) among trials evaluating acid suppressive medications in ANVGIB. Methods: A total of 39 studies using IV PPI drip, IV scheduled PPI, oral PPI, H2-receptor antagonists, and placebo were identified. Network meta-analysis was used for indirect comparisons and Bayesian Markov Chain Monte Carlo methods for calculation of probability superiority. Results: No difference was observed between IV PPI drip and scheduled IV PPI for mortality (relative risk=1.11; 95% credibility interval, 0.56-2.21), LOS (0.04, −0.49 to 0.44), ROS (1.27, 0.64-2.35) and risk of rebleeding within 72 hours, 1 week, and 1 month [(0.98, 0.48-1.95), (0.59, 0.13-2.03), (0.82, 0.28-2.16)]. Oral PPIs were as effective as IV scheduled PPIs and IV PPI drip for LOS (0.22, −0.61 to 0.79 and 0.16, −0.56 to 0.80) and UBT (−0.25, −1.23 to 0.65 and −0.06, −0.71 to 0.65) and superior to IV PPI drip for ROS (0.30, 0.10 to 0.78). Conclusion: Scheduled IV PPIs were as effective as IV PPI drip for most outcomes. Oral PPIs were comparable to scheduled IV for LOS and UBT and superior to IV PPI drip for ROS. Conclusions should be tempered by low frequency endpoints such as ROS, but question the need for IV PPI drip in ANVGIB.